Freedom to Learn at the Rohmatul Umam Islamic Boarding School, Kretek Bantul - Rochim, Ahmad Abdul (Bestari, 2023)
This article departs from the fact that since the beginning, Islamic boarding schools have instilled an attitude of independence, creativity, independent thinking, and innovation in students, by training and fostering them to adapt to society and not depend on others except only God. This is what will later be able to help the students to survive in this 4.0 era, a qualitative field approach (field research). The main data sources of this research are primary data and secondary data. The results of this study are that the Islamic boarding school has one program that is in great demand by the students and also supports the creation of independent learning, namely (free learning in happiness, freedom to think, freedom to innovate, and independent independent and creative) in the Rohmatul Umam Islamic boarding school environment, namely the program Islamic personal development. Because in Islamic personal development, students are given the opportunity to increase their thinking power, creativity, and innovation independently when teaching children and adolescents in mosques.